Cemaran Escherichia coli pada Tepung Telur yang Diimpor Melalui Pelabuhan Tanjung Priok, dan Resistensinya Terhadap Antibiotik (ESCHERICHIA COLI CONTAMINATION ON EGG POWDER IMPORTED THROUGH PORT OF TANJUNG PRIOK AND ITS RESISTANCE AGAINST ANTIBIOTICS) - Sidik, Kamil Riski; Lukman, Denny Widaya; Wibawan, I Wayan Teguh (Jurnal Veteriner; Vol 17 No 2 (2016), 2016)
Eschericia coli contamination was found on egg powder imported to Indonesia during microbialexamination. The study was conducted to describe the presence of E. coli and its resistance to antibioticsin egg powder imported to Indonesia through The port of Tanjung Priok. Samples was determined usingcross sectional study and the sample size was calculated based on assumption of confidence level of 95%with margin of error of 10% and predicted prevalence of 50%. Total of 100 egg powder samples wascollected in August 2014 from two exporting countries, Ukraine (whole egg powder, n=30) and India (wholeegg powder, n=40 and egg yolk powder, n=30). Examination was performed by packaging and label inspectionof the product followed by samples collection and testing for bacterial contamination using rapid test andconventional isolation and identification methods. Detected E. coli was isolated and then tested forantibiotic resistance. Examination results showed that 4 samples were positive to E. coli. E. coli isolatesshowed resistance against 6 types of antibiotics and 75% of the isolates had resistance against minimumof 3 types of antibiotics. These conditions should be taken into consideration since antibiotic resistance inE. coli would cause negative impacts on human, animal and environmental health.
Keywords: antibiotic resistance, egg powder, E. coli